Nigeria’s Foreign Policy Goals in Peacekeeping Operations in Africa - Safiyanu, Sani (Intellectual discourse, 2020)
In line with its foreign policy objectives, Nigeria, since itsindependence, has been participating in Peacekeeping Operations (PKOs)in Africa. It was in recognition of the country’s commitment to the UnitedNations’ (UN) objectives of maintaining peace and security that made itcontribute troops to the UN Operation in the Congo (ONUC) for the first timein 1960. For more than fifty years, Nigeria has continued to make giant stridesand commitment in this regard. This paper examines the benefits it derivesfrom participating in PKOs in Africa under the UN, OAU (now AU) and theECOMOG. Using both primary and secondary data, the paper argues that anormative anxiety was the primary motivating factor for Nigeria’s involvementin PKOs in Africa. This is driven by the idiosyncrasies of the country’s leaderssince its independence in 1960. Nigeria’s decision-makers are confident that itsparticipation in PKOs serves a number of foreign policy goals and provides forthe nation’s interests. The effort promotes the country’s prestige and influencein the comity of nations and in Intergovernmental Organisations (the UN, AUand ECOWAS).